2021
DOI: 10.2147/jir.s318758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photobiomodulation Therapy Combined with Static Magnetic Field in Severe COVID-19 Patients Requiring Intubation: A Pragmatic Randomized Placebo-Controlled Trial

Abstract: Purpose: We aimed to investigate the effects of photobiomodulation therapy combined with static magnetic field (PBMT-sMF) on the length of intensive care unit (ICU) stay and mortality rate of severe COVID-19 patients requiring invasive mechanical ventilation and assess its role in preserving respiratory muscles and modulating inflammatory processes. Patients and Methods: We conducted a prospectively registered, triple-blinded, randomized, placebo-controlled trial of PBMT-sMF in severe COVID-19 ICU patients req… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…On the other hand, current studies demonstrate that PBMT can be an important tool in preventing muscle fatigue, improving performance, and also decreasing atrophy [ 63 , 64 ]. In a recently published study by our research group, we observed clinical improvement and decreased diaphragmatic muscle atrophy in ICU intubated patients when they received a daily application of PBMT [ 16 ]. Therefore, studies that investigate these effects in fatigue-related pathologies, such as chronic fatigue syndrome and LONG-COVID-19, and others, are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, current studies demonstrate that PBMT can be an important tool in preventing muscle fatigue, improving performance, and also decreasing atrophy [ 63 , 64 ]. In a recently published study by our research group, we observed clinical improvement and decreased diaphragmatic muscle atrophy in ICU intubated patients when they received a daily application of PBMT [ 16 ]. Therefore, studies that investigate these effects in fatigue-related pathologies, such as chronic fatigue syndrome and LONG-COVID-19, and others, are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, among the various resources researched to reduce the harmful effects of exercise, low-level laser therapy, also called photobiomodulation therapy (PBMT), has gained prominence [ 16 ]. The PBMT is defined as a form of light therapy that uses non-ionizing light sources, including lasers, light-emitting diodes and/or broadband light, in the visible (400–700 nm) and near-infrared (700–1100 nm) electromagnetic spectrum [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that PBMT could be used to improve COVID-19 patients' respiratory and clinical conditions, decreasing the requirement for ventilator support and ICU stay. Similarly, a placebo-controlled trial of thirty severe COVID-19 patients found that, whilst the length of ICU stay did not change between groups, patients treated with 905/633/850 nm PBMT-sMF (PBMT combined with static magnetic field) showed reduced diaphragm atrophy and improved ventilatory parameters and lymphocyte count [82]. A case report by Sigman et al (2020) used a combination of 808 and 905 nm PBM to treat a 57-year-old man with a severe case of COVID-19 pneumonia.…”
Section: Rationale For Pbmt To Treat Covid-19mentioning
confidence: 99%
“…As a supportive therapeutic strategy, PBMT utilizing a low-level laser (LLLT) raises immunity, stimulate tissue regeneration and decline pro-inflammatory cytokines [ 135 ]. De Marchi et al [ 137 ] studied the treatment of the patients suffering from severe COVID-19, who were in the need of mechanical ventilation, through PBMT-sMF. As they reported, PBMT-sMF could enhance the ventilatory parameters and improve the immune response.…”
Section: Biomedical Applications Of Antiviral Nanomaterialsmentioning
confidence: 99%